2023
DOI: 10.4236/as.2023.142013
|View full text |Cite
|
Sign up to set email alerts
|

Where Are the Bromeliads? A Study on Different Trails in the Ecological Reserve of Guapiaçu, RJ

Abstract: Bromeliaceae are important in ecological restoration, showing easy adaptation to different environments, and constantly interacting with each other through ecological relationships, whose effects may or may not benefit the species involved. The hypothesis tested whether the population density of Hohenbergia augusta is higher in areas at a more advanced successional stage (brown trail), since the species is typical of more structured forest environments, occurring especially in the lower strata of the forest. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…The NMDS result showed that the individuals phorophyte species formed homogeneous and separate groups (Figure 4 influence the establishment and development of this flora. According to Marchiori et al [8], this fact corroborates the discovery of a higher population density of bromeliad epiphytes in areas of more advanced successional stage, due to the presence of a more closed environment with higher humidity. In Brazil, the types of vegetation with the highest number of epiphyte and hemiepiphyte species were forests and campiness with fifty-four and six species, respectively [9].…”
Section: Ripsalis Bacciferasupporting
confidence: 57%
“…The NMDS result showed that the individuals phorophyte species formed homogeneous and separate groups (Figure 4 influence the establishment and development of this flora. According to Marchiori et al [8], this fact corroborates the discovery of a higher population density of bromeliad epiphytes in areas of more advanced successional stage, due to the presence of a more closed environment with higher humidity. In Brazil, the types of vegetation with the highest number of epiphyte and hemiepiphyte species were forests and campiness with fifty-four and six species, respectively [9].…”
Section: Ripsalis Bacciferasupporting
confidence: 57%
“…This emphasizes the importance of the quality of the luminous environment for the initial phase of establishing natural regeneration. Epiphytes are an example of bioindicator plant species present in forests that can indicate environmental disturbances [11], accumulate chemical elements taken from the atmosphere and absorb moisture directly from leaves and stems, become more exposed to pollution, and are useful for assessing the damage caused by pollutants, in addition to being sensitive to burning and deforestation [12].…”
Section: Resultsmentioning
confidence: 99%